Upaya Pengelolaan Sampah Organik melalui Bakul Kompos di Dusun 1 Desa Cisuren - Suhendra Suhendra; Muti’ah Hasanah; Muhammad Heru Dwi S; Ummul Musyarofah; Desy Rahayu; Egi Abdul Aziz (PELITA NUSA TENGGARA, 2026)
Household organic waste management remains a significant environmental issue in rural areas, including Dusun 1, Cisuren Village. The dominance of unmanaged organic waste has the potential to cause environmental pollution and public health problems. This Community Service Program aims to improve community knowledge and skills in managing organic waste through the implementation of the Bakul Kompos method. The program employed an educational approach supported by participatory elements, implemented through socialization activities, demonstrations, and hands-on composting workshops at the household level. The program was conducted in three main stages: collection of organic waste materials, compost processing, and distribution of compost baskets to community members. The results indicate an increase in community understanding of waste segregation and the utilization of organic waste into useful products. In addition to environmental benefits such as reducing the volume of organic waste, the program also provided economic benefits by offering an affordable and environmentally friendly alternative to chemical fertilizers for local farmers. Socially, the program strengthened community participation and awareness regarding environmental cleanliness. Overall, the Bakul Kompos program demonstrates potential as an applicable and sustainable household-based organic waste management model for rural communities.